Plan de negocios para la ampliación de los servicios de la Unidad Educativa Héroes del 41, en la ciudad de Quevedo provincia de Los Ríos. año 2015 - Morales Cabezas, Diana Carolina (2015)
This project is focused on the implementation of a Business Plan for the expansion of the services of the Education Unit 41 Heroes in the city of Quevedo, Province of Rivers, 2015. It claims by market research, technical and economic determine the feasibility of creating a Continuous Training Centre, which will work in the educational establishment, which opened the doors of its facilities to the citizens of Quevedo with the aim of providing users of this institution and potential clients, a alternative for their children spend their time available to acquire new knowledge or strengthen existing ones. To implement the Business Plan's mission, vision and institutional principles which allowed for the clear path of the entity and lay solid foundations for the development of the proposed objective was analyzed. Within this framework, research discusses the problem that focuses the company investigated, besides raising the overall goal and specific objectives, concepts related to the topic of the project are explained, describing the methods to use. Analysis of the results showed the high demand in the market of service offered, which led to a technical proposal which effective administration of this institution may provide a timely manner to immediate decisions that help optimize services that the institution offers its internal and external customers.